MANUSCRIPTS AND PRINTED COPIES OF THE WORK "UṢŪL AL-SHĀSHĪ", THEIR IMPORTANCE TODAY - Abduvahid Ahmadaliev (Western European Studies, 2024)
This article describes the history of Niżām ad-Dīn al-Shāshī's " Uṣūl al-Shāshī", its oldest manuscript and lithographic copies, as well as a detailed description of the work and its components, as well as a commentary, margin, and taliq written on it. This book, which is considered a comprehensive work written in the field of uṣūl al-fiqh, is distinguished by the fact that it has not lost its importance until our time. In the work, not only the areas related to uṣūl al-fiqh, but also the grammar and phonetics of the Arabic language are covered in detail.
Keywords: Uṣūl al-fiqh science; Niżām ad-Dīn al-Shāshī; Uṣūl al-Shāshī